2021
DOI: 10.1186/s12935-021-02210-5
|View full text |Cite
|
Sign up to set email alerts
|

ALDOA inhibits cell cycle arrest induced by DNA damage via the ATM-PLK1 pathway in pancreatic cancer cells

Abstract: Background ALDOA is a glycolytic enzyme found mainly in developing embryos, adult muscle and various malignant tumours, including pancreatic tumours. Our previous study revealed that ALDOA, an oncogene, can promote the proliferation and metastasis of pancreatic tumours. Furthermore, ALDOA could predict poor prognosis in patients with pancreatic tumours. Methods IHC analysis of PDAC tissues was conducted. Western blotting, PCR, cellular IF experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…In the case of ATM, it may be that the binding of ALDOA, directly to ATM or to an ATM-associated complex, may promote the destabilization of the ATM dimer and promote the autophosphorylation and subsequent activation of each ATM molecule. Although ALDOA has not been implicated in regulating ATM activity previously, in contrast to our data, a previous study found that overexpression of ALDOA led to downregulation of ATM levels in pancreatic cancer cells, suggesting that ALDOA levels need to be tightly regulated to avoid disruption of DNA repair pathways 47 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the case of ATM, it may be that the binding of ALDOA, directly to ATM or to an ATM-associated complex, may promote the destabilization of the ATM dimer and promote the autophosphorylation and subsequent activation of each ATM molecule. Although ALDOA has not been implicated in regulating ATM activity previously, in contrast to our data, a previous study found that overexpression of ALDOA led to downregulation of ATM levels in pancreatic cancer cells, suggesting that ALDOA levels need to be tightly regulated to avoid disruption of DNA repair pathways 47 .…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies have indicated that oncogenes enhance glycolysis by increasing the expression of specific glucose transporters and glycolytic enzymes, promoting the proliferation of cancer cells. Studies have shown that ALDOA is included in the pathological processes of various cancers 9 , 12 , 13 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Aldoa induced p53-dependent apoptosis in xenograft tumors in mice [ 40 ]. In pancreatic cancer cells, Aldoa inhibited DNA repair and in consequence promoted cancer development [ 41 ]. The hypothesis that anti-apoptotic mechanisms and those related to DNA repair are involved in TAM action in rat ovaries during the CPA treatment seems to be justified.…”
Section: Discussionmentioning
confidence: 99%